summaryrefslogtreecommitdiff
diff options
context:
space:
mode:
authorAndrey Mokhov <andrey.mokhov@gmail.com>2018-08-29 15:16:51 +0200
committerKrzysztof Gogolewski <krz.gogolewski@gmail.com>2018-08-29 15:16:52 +0200
commit65eec9cfd4410c0e30b0ed06116c15f8ce3de49d (patch)
tree2ea9f0df724a4955ad7523718b44b7ca6d937d34
parent36c1431d9d2d06049190cc0888dbfaee8e2179d6 (diff)
downloadhaskell-65eec9cfd4410c0e30b0ed06116c15f8ce3de49d.tar.gz
Fix a constant folding rule
Summary: One of the constant folding rules introduced in D2858 is: ``` (L y :-: v) :-: (L x :-: w) -> return $ mkL (y-x) `add` (w `add` v) ``` Or, after removing syntactic noise: `(y - v) - (x - w) ==> (y - x) + (w + v)`. This is incorrect, since the sign of `v` is changed from negative to positive. As a consequence, the following program prints `3` when compiled with `-O`: ``` -- This is just subtraction in disguise minus :: Int -> Int -> Int minus x y = (8 - y) - (8 - x) {-# NOINLINE minus #-} main :: IO () main = print (2 `minus` 1) ``` The correct rule is: `(y - v) - (x - w) ==> (y - x) + (w - v)`. This commit does the fix. I haven't found any other issues with the constant folding code, but it's difficult to be certain without some automated checking. Reviewers: bgamari, tdammers Subscribers: hsyl20, tdammers, rwbarton, carter GHC Trac Issues: #15569 Differential Revision: https://phabricator.haskell.org/D5109
-rw-r--r--compiler/prelude/PrelRules.hs2
1 files changed, 1 insertions, 1 deletions
diff --git a/compiler/prelude/PrelRules.hs b/compiler/prelude/PrelRules.hs
index 695e879ba2..80cfa20ba3 100644
--- a/compiler/prelude/PrelRules.hs
+++ b/compiler/prelude/PrelRules.hs
@@ -1783,7 +1783,7 @@ numFoldingRules op dict = do
(v :-: L y) :-: (w :-: L x) -> return $ mkL (x-y) `add` (v `sub` w)
(v :-: L y) :-: (L x :-: w) -> return $ mkL (0-x-y) `add` (v `add` w)
(L y :-: v) :-: (w :-: L x) -> return $ mkL (x+y) `sub` (v `add` w)
- (L y :-: v) :-: (L x :-: w) -> return $ mkL (y-x) `add` (w `add` v)
+ (L y :-: v) :-: (L x :-: w) -> return $ mkL (y-x) `add` (w `sub` v)
(x :++: w) :-: (y :++: v) -> return $ mkL (x-y) `add` (w `sub` v)
(w :-: L x) :-: (y :++: v) -> return $ mkL (0-y-x) `add` (w `sub` v)
(L x :-: w) :-: (y :++: v) -> return $ mkL (x-y) `sub` (v `add` w)